FAMILY AND WORK RESPONSIBILITIES AND COPING STRATEGIES OF WOMEN ACADEMICS - Fatoki, F. T; Kobiowu, S. V (European Scientific Journal, ESJ, 2015)
The study determined the relative weights of the different components of family and work responsibilities (giving birth, raising children, care giving, house chores, supportive or unsupportive spouse, research, teaching and administration services, etc) on the career progression of women in academic and also, identified the strategies employed in striking a balance between the family and the work place responsibilities. This was with a view to improve career progression of women academics. This study adopted a descriptive survey design. The population for this study consisted of female lecturers in tertiary institutions in Osun State. Two universities were purposively selected based on ownership (public and private) and year of establishment. Also, two polytechnics were purposively selected, one Federal and one State-owned. One College of Education was selected using simple random sampling technique. All the female lecturers in the selected institutions constituted the sample. A self-developed questionnaire titled â€œQuestionnaire on Family/Work Issues and Career Progressionâ€ (QFWICP) was used to collect relevant data for the study. The reliability of the QFWICP using Cronbach Alpha Coefficient was 0.824. Data collected for the study were analysed using, descriptive statistics and Multiple Regression. The results showed that, family responsibility as a whole has a significant weight on women academics career progression with the constant unstandardized coefficient (Beta = 2.091, t = 24.908, p < .05). However, child bearing (Beta = -0.406, t = -5.283 p < .05), care giving (Beta = -0.268, t = -3.986, p< .05) and house chores (Beta = -0.195, t = -2.846 p < .05) were significant predictors of women academic progression. It was also revealed that active support from spouse/partner when there is need to stay late at work, travel for conference etc, making use of childcare centres close to the workplace (i.e. day care) and annual leave respectively are very effective in coping with family- work responsibilities effects on their academic careers. The study concluded that the career progression of women in academic is affected by the family responsibilities and thus recommend that women academics need good coping strategies to ameliorate the effect.